Etiological and epidemiological features of acute respiratory infections in China - Zhong-Jie Li (Nature Portfolio, 2021)
China operates a national surveillance program for acute respiratory infections and sampled over 200,000 patients between 2009–2019. Here, the authors present results from this program and describe patterns by age, pathogen type, presence of pneumonia, and season.